2009
DOI: 10.1007/s12273-009-9119-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the saving potential of blind controller via multi-objective optimization

Abstract: This paper presents the results of computational experiments where multi-objective algorithms were used to tune a controller for blind movements in a residential building and a room of the LESO (Solar Energy and Building Physics Laboratory) experimental building. The blind controller, which is based on fuzzy logic, was optimized not only in terms of energy consumption but also in terms of thermal comfort. The goal is to show saving potential for intelligent blind controller in a real world example rather than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…According to the BS EN ISO 7730 [3] the accepted range of comfort is defined as PMV˛[À0.5, 0.5] according to that we define the answers Très chaud, Chaud, Légèrement chaud, as too hot; the answers Très froid, Froid as Légèrement frais, too cold; and the central answers Comfortable, as comfortable. 2 (Table 1). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the BS EN ISO 7730 [3] the accepted range of comfort is defined as PMV˛[À0.5, 0.5] according to that we define the answers Très chaud, Chaud, Légèrement chaud, as too hot; the answers Très froid, Froid as Légèrement frais, too cold; and the central answers Comfortable, as comfortable. 2 (Table 1). …”
Section: Discussionmentioning
confidence: 99%
“…Additional, the opening of the windows and the set point of the HVAC system are other central issues. Nevertheless, in a previous publication of the first author it has been shown that blind operation has a strong impact on energy consumption of a building [2,15]. It is essential for the blind control to define solar gains allowance during daytime in order to save heating energy in the evening and during night time.…”
Section: Scope Of Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Simulation-assisted optimization strategies in building design are today mostly used for fine-tuning in specific, later-stage types of inquiry (Augenbroe, 2003), characterized by relatively clear goals and relatively few variables in play; or targeted to specific, constrained types of problems, determined by building type, or use, or objective function, and by the selection of specific issues of inquiry (Daum et al, 2009;Shin, 2011;Khan et al, 2012). This happens in spite of the fact that the variables influencing building performance are numerous and interrelated.…”
Section: Search In Building Designmentioning
confidence: 99%